INFLUENCE OF DIFFERENT LEVELS OF BIOFERTILIZER EM1 AND NITROGEN FERTILIZER ON GROWTH TRAITS AND YIELD IN WHEAT - Saleh Ibraheem (Mesopotamia Journal of Agriculture)
Afield experiment was carried out during the winter seasons of 2008-2009 and 2009-2010 in Salamya which is located at 34 Km southern from Mosul city. The split plot arrangement in Randomized Complete Block Design (R.C.B.D) with three replications was used. The experiment included four levels of biofertilization EM1 (0, 1, 2, 3 cc/Liter), five levels of nitrogen fertilization (0,30,60,90,120Kg N/ha). Nitrogen fertilization levels and biofertilization EM1 were represented as Main plots, and sub plots respectively. The results indicated that biofertilization EM1 level 3 cc/Liter was significantly superior in all growth traits and yield in both seasons with the exception of harvest index in first season it was significantly superior in stem length, leaf area, biological yield, number of spike per m2, spike length, number of grains per spike, weight of 1000 grains, grain yield,protein percentage and yield.Nitrogen fertilization level 120Kg N/ha was significantly superior in all growth traits and yield witch is stem length, leaf area, biological yield, number of spike per m2 , spike length, number of grains per spike, weight of 1000 grains, grain yield, harvest index,  protein percentage and yield in both seasons . Biofertilization EM1 and Nitrogen fertilization interacted significantly for all growth and yield characters in both seasons, biofertilization EM1 level 3 cc/Liter and Nitrogen fertilization level 120Kg N/ha  interaction was significantly superior in all growth traits and yield in both seasons with the exception of harvest index which was at the interaction between biofertilization EM1 level1cc/Liter and nitrogen fertilization level 120Kg N/ha.